School Closures in Rural Finnish Communities - Outi Autti; Eeva Kaisa Hyry-Beihammer (Journal of Research in Rural Education, 2014)
The network of small rural schools in Finland has been radically weakened since the global recession of the 1990s. This article focuses on the social role of rural schools and the phenomenon of school closures. Our aim is to look at rural schools from the viewpoint of local residents and examine how they experience school closures. We seek to hear the local voice that often remains silent in closure processes. The contributions to rural education research rise from the Finnish context and from the interview data, which incorporate multiple local stakeholder perspectives regarding rural schools and the rural school-community connection. The study uses empirical data collected from interviews with people who have experienced school closures in their villages or municipalities. Social capital is used to understand the role of a school in the community: We study its role as a producer and maintainer of local social capital.